Engineering Education Quality Assurance A Global Perspective - Patil, Arun; Gray, Peter (Springer US : Imprint: Springer, 2009)
Engineering Education Quality Assurance: A Global Perspective provides a world-wide view of the history and the current conditions of Engineering Education Quality Assurance. This book provides the first wide-ranging picture of Quality Assurance schemes from essentially every continent and the issues related to their development and implementation. In addition, a generic Engineering Education Quality Assurance Model is described that synthesizes all of the extant approaches and provides a structure for future development. The book begins with an overview of the history and background of Quality Assurance in higher education and Engineering Education over the past century. This is followed by a discussion of the general issues and challenges facing Quality Assurance in the 21st century from global, regional and national perspectives. Then the history and current conditions of Engineering Education Quality Assurance in a sample of ten different countries around the world are discussed. The last section provides a variety of strategies and techniques to aid in the development and institutionalization of effective Quality Assurance approaches. Engineering Education Quality Assurance: A Global Perspective brings together leading academics and professionals from fifteen different countries who share their wealth of experience and insights. Their collective expertise provides a snap-shot of the current state of Quality Assurance in higher education and Engineering Education, an explanation of how we got to where we are, and a road-map for the future.